Respuesta :
Answer:
-2/3
Step-by-step explanation:
To find the slope, we use the formula
m = ( y2-y1)/(x2-x1)
= ( 3 -7)/( 0 - -6)
= (3-7)/(0+6)
= -4/6
= -2/3
Answer:
m = -2/3
Step-by-step explanation:
Here, we need to find the slope .
To find slope we are using slope formula .
Slope Formula, m = ( y² - y¹ ) / ( x² - x¹ )
Where, we have given
- x¹ = -6 and x² = 0
- y¹ = 7 and y² = 3
Now putting the given values in the formula.
Slope , m = ( 3 - 7 ) / ( 0 - (-6 ) )
- m = ( -4 ) / ( 6 )
Divide by 2.
- m = -2 / 3
Therefore, Your answer is -2/3.